Outside directors on the board, competition and innovation - Achim Buchwald; Susanne Thorwarth (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
We investigate the influence of non-executive outside directors on firms' innovative performance for a sample of 1,393 listed firms in the EU - 15 member states plus Norway and Switzerland in the period 2005 to 2010. Our results show that the fraction of non-executive outside directors on the board is associated with a significant decrease in the number of patent applications if competition in the market is low. This may indicate that restrictive monitoring and lower advising competences of outside directors mitigate executives' incentives to innovate. In industries with effective competition, the negative influence of outsiders is offset by the pressure to focus on innovation strategies.
Keywords: G34; L14; L25; M21; O31; 330; Competition; Corporate Governance; Innovation; Patents; Board Composition; Outside Directors